Data Stories of Water: Studying the Communicative Role of Data Visualizations within Long‐form Journalism - Garreton, M.; Morini, F.; Paz Moyano, D.; Grün, G.‐C.; Parra, D.; Dörk, M. (Computer graphics forum, 2023)
We present a methodology for making sense of the communicative role of data visualizations in journalistic storytelling and share findings from surveying water‐related data stories. Data stories are a genre of long‐form journalism that integrate text, data visualization, and other visual expressions (e.g., photographs, illustrations, videos) for the purpose of data‐driven storytelling. In the last decade, a considerable number of data stories about a wide range of topics have been published worldwide. Authors use a variety of techniques to make complex phenomena comprehensible and use visualizations as communicative devices that shape the understanding of a given topic. Despite the popularity of data stories, we, as scholars, still lack a methodological framework for assessing the communicative role of visualizations in data stories. To this extent, we draw from data journalism, visual culture, and multimodality studies to propose an interpretative framework in six stages. The process begins with the analysis of content blocks and framing elements and ends with the identification of dimensions, patterns, and relationships between textual and visual elements. The framework is put to the test by analyzing 17 data stories about water‐related issues. Our observations from the survey illustrate how data visualizations can shape the framing of complex topics.